Using Plastic Money (Cards) in Kathmandu Valley: Users’ Knowledge, Current Use, Challenges and Way-forward - Devkota, Niranjan; Shakya , Bikesh; Parajuli, Seeprata; Poudel, Udaya (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
This study aims to understand the users’ knowledge about plastic money, its current use, challenges they faced and way-forward. Based on descriptive research design, primary data is used for the purpose as per its suitability. A structured questionnaire has been arranged with the help of KOBO and devised for the information assortments from 404 plastic money users. Results found that people who use plastic money usually work in banks and financial institutions (33.87%) and are from the nuclear family (62.62%), with income between 25001 – 50000 (56%). 95.79 % of the respondents know about plastic money, and 86.3 % have plastic money. 88 % of respondents said they feel safe while using plastic money. 40.72% of respondents have faced challenges and problems while using plastic money. The majority (79.28%) of respondents believed that using the bank's services could be solved. It can be solved by giving training (34.85%), quick response to the problem raised by users (44.32%), update technology (34.47%) and keep a good network in the ATMs (71.79%) and quick solutions to the user's problems (75.76%). This study concludes that hassle-free transactions, a low-interest rate of credit cards, attractive advertisement, and awareness of how plastic money can use help and attract users of plastic money. .